Review of Sean Gallagher, James Haar, John Nadas, and Timothy Striplin, eds. Western Plainchant in the First Millennium: Studies in the Medieval Liturgy. Burlington, VT: Ashgate, 2004 - Dohoney, Ryan W. (Current Musicology, 2003)
The untimely passing of James McKinnon in 1999 remains a point of great sorrow not only among scholars of medieval liturgy and chant but also among the musicological community at large. The publication of his magnum opus The Advent Project (2000) and subsequent scholarly debate sparked by its provocative history of the composition of Roman Mass Propers have insured that his legacy will remain vital to students of chant and religious studies for decades to come. As Kenneth Levy notes in his contribution to Western Plainchaint, the first millennium was the “Lake Erie of [McKinnon’s] musicological boatings” (231). Beginning with his publication in the first issue of Current Musicology, James McKinnon was a tireless investigator into the music of the Christian liturgy from late antiquity through the early Middle Ages. While his initial work explored the place of instruments within the music of the Christian liturgies of the first millennium (1965), his later work focused on the organization and development of the Roman Mass. In the mid-1980s, McKinnon began ambitious studies into the origins of the Mass Proper. His examination of psalmody in the ancient synagogue argued that psalmody did not have its origins in Jewish practice as thought by earlier scholars such as Peter Wagner (McKinnon 1986). Instead, McKinnon posited a late fourth-century “psalmodic movement” that popularized psalm-singing in monastic communities and led to the formation of the Gradual as psalm-singing became a greater part of both monastic and lay liturgical expression (1987; 1994).